EduCardia: A Modern Technology-Powered Methodology for the Assessment and Improvement of Social and Emotional Competencies of Students in K12 Schools - Eleni Fotopoulou; Elia Lopez Cassa; Lydia Mavraidi; Julia Peris; Anastasios Zafeiropoulos; Adina Colomeischi; Christina Papasolomontos; Symeon Papavassiliou (IEEE Access)
The application of Social and Emotional Learning (SEL) methodologies within classrooms has been widely adopted and examined, highlighting its positive impact on the academic, emotional, and social sectors at both the individual and classroom levels. Through this wide applicability, a need is identified to focus more on the development of SEL approaches that support the integration of the various parts of a SEL methodology (e.g., planning, implementation, monitoring and assessment). Such approaches should not underestimate the value of the SEL assessment. It is necessary to engage both the developers and the practitioners of SEL methodologies and provide tools to assist teachers to better interpret the collected data and results and plan targeted SEL activities. Motivated by such needs, we detail the EduCardia SEL methodology, which focuses on the provision of a set of guidelines and tools to assess and improve the social and emotional competencies of students in primary and secondary educational levels, taking advantage of Information and Communication Technologies (ICT). The EduCardia SEL methodology considers the integration of the various parts of a SEL methodological approach and supports continuous assessment processes while offering user-friendly interfaces to interpret the produced results. Evaluation results are provided based on the application of the EduCardia SEL methodology in K12 schools in Greece for a short period of time, considering three different age groups. The targeted competencies are shown to be improved, while teachers provide insights on the applicability and efficiency of the proposed approach.